2012
DOI: 10.2214/ajr.11.8204
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolesion of the Liver on Gadoxetate Disodium-Enhanced MR Images Obtained After Transarterial Chemoembolization for Hepatocellular Carcinoma: Clinicoradiologic Correlation

Abstract: The prevalence and appearance of pseudolesions differ at different intervals from TACE. Radiologists need to recognize the clinicoradiologic characteristics to differentiate pseudolesions from true residual or recurrent HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Shinagawa et al . reported that parenchymal changes can occur after TACE . However, our results showed good data fit, with R 2 values ranging from 0.76 to 0.99, and the patterns of reduced parenchymal enhancement were similar between previous treated and untreated lesions.…”
Section: Discussionsupporting
confidence: 53%
“…Shinagawa et al . reported that parenchymal changes can occur after TACE . However, our results showed good data fit, with R 2 values ranging from 0.76 to 0.99, and the patterns of reduced parenchymal enhancement were similar between previous treated and untreated lesions.…”
Section: Discussionsupporting
confidence: 53%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…Additionally, it is reported that gadoxetate disodium‐enhanced MRI can predict the patient prognosis because hyperintense HCC in the hepatobiliary phase have biologically less aggressive features than those of hypointense HCC . On the other hand, gadoxetate disodium‐enhanced MRI frequently shows pseudolesions in follow‐up studies after cTACE, as well as artifacts in the arterial phase of dynamic study. In a report by Shinagawa et al.…”
Section: Discussionmentioning
confidence: 99%